2014
DOI: 10.1190/geo2013-0399.1
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature dielectric measurements of confined water in porous granites

Abstract: The dielectric behavior of rocks affected by the known phase transition of supercooled water is the main problem we analyzed. Three different granitic rocks were used to perform dielectric measurements in the frequency range from 100 Hz to 1 MHz and temperatures 100-350 K. Thin cylindrical samples were prepared, and circular electrodes were established using silver conductive paint. A clear change in the dielectric measurements appears at T ∼ 220 K for one of the samples. This coincides with the known phase tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Nevertheless, in Silva et al (2014), it was not possible to identify which were the minerals that retained the adsorbed water clusters and consequently where the water-rock interaction forces should be stronger. Such forces would probably be a result of hydrogen bond formation between absorbed water clusters and the rock minerals (Osipov, 2012).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Nevertheless, in Silva et al (2014), it was not possible to identify which were the minerals that retained the adsorbed water clusters and consequently where the water-rock interaction forces should be stronger. Such forces would probably be a result of hydrogen bond formation between absorbed water clusters and the rock minerals (Osipov, 2012).…”
Section: Introductionmentioning
confidence: 93%
“…The analysis revealed that those samples had a low percentage of hydration water in their structure, and for that reason it was argued that adsorbed water, at the rock pores, was resistant to drying and should play the dominant role in the relaxation (Silva et al, 2014). Actually, impedance spectroscopy (IS) at the supercooled water phase transition is sensitive to very small amounts of water (Gomes et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations